Carbonate budgets induced by coral restoration of a Great Barrier Reef site following cyclone damage - Nuñez Lendo, C. Isabel; Suggett, David J.; Boote, Chloë; McArdle, Alicia; Nicholson, Freda; Fisher, Eric E.; Smith, David; Camp, Emma F. (Frontiers in Marine Science, 2024)
Coral carbonate production is fundamental to reef accretion and, consequently, the preservation of essential reef ecosystem services, such as wave attenuation and sustained reef biodiversity. However, the unprecedented loss of coral reefs from anthropogenic impacts has put these valuable ecosystem services at risk. To counteract this loss, active rehabilitation of degraded reef sites has accelerated globally. A variety of restoration practices exist, tailored to local site needs and reef types. For sites where there is a significant unconsolidated substrate, Mars Assisted Reef Restoration System (MARRS, or “Reef Stars”) has been utilised to contribute toward rubble stabilisation and reef accretion. However, the effect of the Reef Stars on the local carbonate budgets and structural complexity has not been assessed. For that purpose, we assess coral cover and reef complexity through a census-based approach to identify the contribution of carbonate producers and eroders alongside studying coral skeletal properties to estimate current carbonate budgets on a rehabilitated site compared to natural unrehabilitated reef and rubble patches on the mid-Great Barrier Reef. Our research identified positive ecological processes and ecological functions such as increased carbonate budget, coral cover and structural complexity at the restored site compared to the non-intervened reef and rubble patches. In general, no impacts on skeletal rigour relative to this active reef restoration were found for two key coral species and the Acropora rubble for most of the skeletal traits. However, Pocillopora damicornis hardness seemed to decrease on the restored site compared to the other sites, demonstrating different performances of coral species during restoration activities that should be considered to maximise return-on-effort of restoration activities. Overall, our data demonstrate that consideration of carbonate budgets is important for measuring success of coral restoration initiatives and that coral restoration can be a relevant tool to recover lost local carbonate budgets.